Information, the Cost of Credit, and Operational Eﬃciency: An Empirical Study of Microfinance - Garmaise, Mark J.; Natividad, Gabriel (Review of Financial Studies, 2010)
We provide direct evidence on the impact of asymmetric information on both financing and operating activities through a study of credit evaluations of microfinance institutions (MFIs). We employ a regression discontinuity model that exploits the eligibility criteria of an evaluation subsidy oﬀered by a nonprofit consortium. Evaluations dramatically cut the cost of financing. This eﬀect is strongest for commercial lenders and for short-term MFI–lender relationships. The impact of evaluations on the supply of finance is mixed. Evaluated MFIs lend more eﬃciently, extending more loans per employee.